TOLERANSI BERAGAMA DI KABUPATEN POSO - Ahsanul Khalikin (Harmoni, 2016)
This paper describes the dynamics of religious life in the aftermath of religious conflict in Poso. The findings show that Poso is inevitably a plural society both ethnicity and religion. The relationship between families and interreligious marriage have been in practice since in the old times and there is no problem with that. Prior to the Poso conflict occurring in 1998, 2000 and 2001 respectively, Poso city was a predominantly Muslim area. While the Christian people reside in the highland areas. This religious topography changed dramatically in the post Poso conflict. In the past, Poso people lived harmoniously and respected the outsiders very well. This research used qualitative approach and case study as its method. Data collection includes interviews and observation. The conclusion is that, religious tolerance among Poso people prior to the conflict was based on Sintuwu Maroso. The meaning of this philosophy is twofold: sintuwu means to unite or unity, and maroso means being strong. Therefore, the two words mean ‘a strong unity’. Poso people are always pleased to live peacefully and the old philosophy is often instrumental to solve conflict in the society